Stinging Insect Allergy A Clinician's Guide - Freeman, Theodore M.; Tracy, James M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This comprehensive book thoroughly covers the field of stinging insect allergy; addressing all clinical aspects, including diagnosis and therapeutic recommendations. Stinging Insect Allergy: A Clinician$1 (Bs Guide begins with a look into the entomologic aspects of Hymenoptera insects (bees, vespids, wasps and ants), which cause nearly all the IgE mediated reactions due to insects. Further chapters single out and examine the unique aspects of common Hymenoptera species, such as bees and fire ants, in rich detail. Later chapters clinically review what is known about non-Hymenoptera biting insects, such as mosquitoes. In addition, multiple chapters address the overlap of Hymenoptera allergy as practiced in North America and Europe, as well as other sciences. Final chapters cover the impact ecology is having on insect allergy; and the impact insect allergy is having on other areas of medicine, such as mast cell disorders. Stinging Insect Allergy: A Clinician$1 (Bs Guide is an ideal resource for medical students, residents, allergists, and general practitioners alike, and also serves as an important reference text for any practitioner of allergy and immunology who desires a complete picture of Hymenoptera and non-Hymenoptera insect allergy. .s
Preface -- Part 1 -- 1. History of Hymenoptera Allergy -- 2. Entomological Aspects of Insect Sting Allergy -- 3. Hymenoptera Venoms: Toxicity, Components, Stability and Standardization -- 4. Clinical Aspects of Hymenoptera Allergy: IgE Response Stings and Immunotherapy -- 5. Diagnostic In Vivo and In Vitro Methods in Insect Allergy -- 6. Pathologic Findings in Hymenoptera Sting Fatalities -- 7. Treatment of Hymenoptera Reactions: Acute and Prophylactic -- 8. Adverse Reactions to Skin Testing and Immunotherapy with Hymenoptera Venoms and Whole Body Extracts -- 9. Duration of Venom Immunotherapy -- Part 2 -- 10. Unique Aspects of Bee Allergy and Reactions -- 11. The Imported Fire Ant: The United States Experience -- 12. Mosquito Hypersensitivity: Clinical Updates -- 13. Allergic Reactions to Biting Insects -- 14. Arthropods and Human Diseases -- Part 3 -- 15. Behavior, Ecology, Natural History and Distribution of Stinging Hymenoptera -- 16. Insect Sting Allergy and Mast Cell Disease -- 17. Current Remaining Questions.
Keywords: Medicine; Immunology; Allergy; Entomology; Medicine & Public Health; Allergology; Entomology; Immunology